1977
DOI: 10.1128/iai.16.1.226-231.1977
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on lymphocyte-mediated cellular immunity in murine histoplasmosis

Abstract: Peritoneal exudate cells from immunized mice inhibit the intracellular growth of Histoplasma capsulatum. The lymphocyte is the mediator cell of this phenomenon. Lymphocytes from immunized animals are highly activated cells. Supernatants from cultures of immune lymphocytes or from cultures of mitogenstimulated lymphocytes did not arm macrophages from normal animals to inhibit the intracellular growth of H. capsulatum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Studies by others suggest that the critical event terminating H. capsulatum replication is macrophage activation (9,14,15,27). Howard found that intact lymphocytes derived from histoplasma-immune mice could activate macrophages from either immune mice or nonimmune mice, enabling them to inhibit intracellular growth of H. capsulatum (14,15). The status of CMI in nu/nu mice is somewhat paradoxical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by others suggest that the critical event terminating H. capsulatum replication is macrophage activation (9,14,15,27). Howard found that intact lymphocytes derived from histoplasma-immune mice could activate macrophages from either immune mice or nonimmune mice, enabling them to inhibit intracellular growth of H. capsulatum (14,15). The status of CMI in nu/nu mice is somewhat paradoxical.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters often revert to negative in people with disseminated histoplasmosis (17,25). Control of histoplasmosis is apparently achieved through T-lymphocyte intervention, which leads to macrophage activation (13)(14)(15). However, there are many unanswered questions concerning the character and specificity of cell-mediated immune processes and the role of antibody in host defense in histoplasmosis (8,10,17,19,25).…”
mentioning
confidence: 99%
“…In contrast to the killing of extracellular bacterial pathogens, resident macrophages are relatively inefficient in killing certain fungal pathogens, e.g., Candida albicans (21, 30) and Cryptococcus neoformans (11,14,23). Howev-er, activated macrophages are more effective in killing these pathogens (14, 30) and can kill facultative intracellular fungal pathogens, e.g., Histoplasma capsulatum (17,18) or Coccidioides immitis (4,5).…”
mentioning
confidence: 99%
“…It is generally held that a critical host defense mechanism activated in response to infection by Histoplasma capsulatum is the so-called cellmediated immune response. Support for this concept is provided by several experimental studies: first, by the demonstration that lymphocytes from mice immunized by sublethal infection with H. capsulatum can mediate suppression of intracellular growth of the fungus in normal mouse macrophages (17); second, by demonstration of increased susceptibility to Histoplasma infection in congenitally athymic mice (38) or in conventional mice after treatment with antilymphocyte serum and cytotoxic agents (1,8,12); and third, by evidence for transfer of adoptive immunity against Histoplasma by spleen or peritoneal cells from immunized donors (36).…”
mentioning
confidence: 99%